2022
DOI: 10.1136/bmjopen-2022-064499
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health hazards among healthcare providers and ancillary staff in Ghana: a scoping review

Abstract: ObjectiveThe strict implementation of occupational health and safety policy curbs exposure to occupational hazards. However, empirical evidence is lacking in the Ghanaian context. This review primarily aimed to explore exposure to occupational hazards among healthcare providers and ancillary staff in Ghana.DesignA scoping review was conducted based on Arksey and O’Malley’s methodological framework and Levacet al’s methodological enhancement.Data sourcesSearches were conducted of the PubMed, MEDLINE, CINAHL, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
(170 reference statements)
0
1
0
Order By: Relevance
“…⇒ In this study conducted among healthcare support staff within 10 hospitals in the Greater Accra region, Ghana, it was found that being a healthcare assistant was associated with a higher prevalence of exposure to needlestick injury while being married, had training on standard precaution, being a supervisor and non-existence of needlestick reporting systems were linked to lower prevalence of exposure. BMJ Public Health 44.5% 8 while the annual prevalence of needlestick injury ranged from 39.0%-91.0% 9 to 14.0%-60.0% 10 in Africa and Ghana, respectively.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…⇒ In this study conducted among healthcare support staff within 10 hospitals in the Greater Accra region, Ghana, it was found that being a healthcare assistant was associated with a higher prevalence of exposure to needlestick injury while being married, had training on standard precaution, being a supervisor and non-existence of needlestick reporting systems were linked to lower prevalence of exposure. BMJ Public Health 44.5% 8 while the annual prevalence of needlestick injury ranged from 39.0%-91.0% 9 to 14.0%-60.0% 10 in Africa and Ghana, respectively.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The global picture of lack of data, and low research on needlestick injury among healthcare support staff is similar to the situation in Africa and other developing countries, 9 15 where few studies have addressed needlestick injury among orderlies and medical waste handlers. 16 17 According to a recent scoping review on exposure to occupational health hazards among healthcare providers and healthcare support staff of the Ghanaian healthcare industry, 10 no study addressed needlestick injury among the support staff of the healthcare industry; hence, the reason for the conduct of this study. This research, therefore, investigated the prevalence and determinants of exposure to needlestick injury among healthcare support staff in the populated Greater Accra region of Ghana.…”
Section: How This Studymentioning
confidence: 99%
“…In the Ghanaian setting, exposure to workplace violence among health workers has been widely rumoured, but there is insufficient evidence on the issue [ 14 ]. A few available studies depicted that about 9.0–73.9% cases of workplace violence are experienced by health workers in Ghana [ 14 17 ]. Boafo et al‘s study revealed that 12.0% and 52.2% of nurses in Ghana are sexually harassed and verbally abused, respectively.…”
Section: Introductionmentioning
confidence: 99%